Pengaruh Pemahaman Akuntansi Dasar, Computer Attitude Dan Computer Anxiety Terhadap Keahlian Pemakaian Software Akuntansi Pada Siswa Jurusan Akuntansi Di Smk Dwijendra Denpasar - Anak Agung Ardiantari; Ni Wayan Yuniasih; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2023)
This study aimed to determine the impact of basic accounting understanding, computer attitudes, and computer fears on their expertise in using accounting software among accounting students at SMK Dwijendra Denpasar. is. The population used in this study was all active students in SMK Dwijendra Denpasar's accounting program, a total of 130 students. The sample size for this study was 41 individuals identified by a targeted sampling technique and tested using multiple linear regression analysis techniques. The results of this study show that understanding basic accounting has a positive and significant effect on accounting software proficiency. Computer settings do not affect the use of accounting software. Fear of computers does not affect your ability to use accounting software. Looking at the results of this research, I hope that accounting students will continue to study without being satisfied and improve their skills and abilities using accounting software. world. Not only can students make effective use of their study time at school, but they can also improve their accounting software skills by reading books about accounting software and watching YouTube at home. make it possible. accounting software.